Alveolar biomodification as an indispensable procedure before guided bone regeneration - Daniel Del Rio; Andres Romero; Antonio Jose Díaz Caballero (Editorial Ciencias Médicas, 2020)
Introduction: The placement of dental implants is based on the creation of optimal conditions in the remnant bone. In some cases, it is indispensable to perform bone regeneration procedures and use barrier membranes to create such optimal conditions capable of favorably supporting the dental implant. Objective: Describe alternatives of barrier membranes in cases of guided bone regeneration. Case report: A female 53-year-old patient presents with a gingival fistula attached to tooth 14. Root fracture is diagnosed and extraction is conducted. Next, alveolar biomodification is performed to carry out guided bone regeneration and placement of a fibrin-rich plasma membrane. When healing is complete dental implants will be placed. Conclusions: The use of barrier membrane alternatives has shown to be effective in cases of guided bone regeneration.